Development of a Miniature Laser-Induced Underwater Shockwave- Generating Device using an Optical Fiber - Nakamura, Masanori; Shibutani, Hideo (Micro and Nanosystems, 2015)
Shockwaves are widely used in clinical practices with applications including orthopedics, traumatology and lithotripsy. Its use as a therapeutic agent has also gained attention following reports that shockwaves enhance neoangiogenesis and cell proliferation. However, shockwave-generating devices are large, and therefore not suitable for endoscopic and endovascular operations. As such, we attempted to develop a miniature shockwave-generating device using an optical fiber with a 1 mm diameter. The tip of an optical fiber was finely polished, finished with chemical agents, and coated with a titanium film by vacuum evaporation. A pulse laser was applied to the titanium film through the optical fiber, and a shockwave was induced by thermoelastic effects. Finally, the shockwave released from the tip of the fiber was visualised in a water tank with a shadowgraphic technique, and the pressure was measured. The results showed that the shockwave pressure varied depending on whether the fiber tip was polished and whether the film was cracked. In the polished fibers with less cracked films, the shockwave pressure reached 0.3 MPa when a laser with the power density of 80 GW/m2 was introduced. Given the same laser power density, the shockwave pressure decreased by approximately 40% when the fiber tip was not polished and when the film was more cracked. These results highlighted the importance of strict quality control of the surface texture and the metallic film of the optical fibers when generating strong shockwaves.
Keywords: shadowgraph